The Sumenep Government's Tourism Diplomacy Strategy and its Impact on the Sumenep`s Economic Growth in 2021—2023 - Alim, Moh Zahirul (Universitas Muhammadiyah Malang, 2024)
Diplomacy activities in its implementation are not only carried out by the state with the central government as the main actor. In an effort to achieve regional development interests and goals in the fields of culture, tourism and economy, for example, district governments (pemda) also play an important role in practicing diplomacy. The Sumenep regency government is currently one of the districts in Indonesia that is very active in conducting tourism diplomacy. In developing the tourism sector, the Sumenep regency government applies a pentahelix strategy, which involves the involvement of five important elements in tourism: government, academics, bureaucracy, entrepreneurs and the media. In addition, in facilitating the internationalization of tourism, the Sumenep regency government specifically conducts paradiplomacy with international circles. This study found that the tourism diplomacy strategy carried out by the Sumenep regency government is effective in bringing in domestic and foreign tourists, which then has a significant impact on increasing the economy of the Sumenep regency.